CXCR4-targeted Theranostics in Hematooncology: Opportunities and Challenges - Werner, Rudolf; Haug, Alexander; Buske, Christian; Heidegger, Simon; Illert, Anna L.; Bassermann, Florian; Herhaus, Peter; Buck, Andreas; Duell, Johannes; Topp, Max S; Kraus, Sabrina; Einsele, Hermann; Lapa, Constantin; Raderer, Markus; Lenz, Georg; Habringer, Stefan; von Tresckow, Bastian; Keller, Ulrich (Nuklearmedizin - NuclearMedicine, 2024)
C-X-C motif chemokine receptor 4 (CXCR4) is overexpressed in a multitude of cancers, including neoplasms of hematopoietic origin. This feature can be leveraged by a theranostic approach, which provides a read-out of the actual CXCR4 expression in vivo, followed by CXCR4-targeted radioligand therapy (RLT) exerting anti-cancer as well as myeloablative efficacy. In a recent meeting of hematooncology and nuclear medicine specialists, statements on the current clinical practice and future perspectives of this innovative concept were proposed and summarized in this opinion article. Experts concluded that i) CXCR4-directed [68Ga]Ga-PentixaFor PET/CT has the potential to improve imaging for patients with marginal zone lymphoma; ii) CXCR4-targeted RLT exerts anti-lymphoma efficacy and myeloablative effects in patients with advanced, treatment-refractory T-cell lymphomas; iii) prospective trials with CXCR4-based imaging and theranostics are warranted.
Keywords: CXCR4; chemokine receptor; theranostics; marginal zone lymphoma; T-cell lymphoma; [68Ga]Ga-PentixaFor